Stability Indicating RP-HPLC Assay Method for Estimation of Dronedarone Hydrochloride in Tablet - Atul T Hemke, Shivshanker Kukade, Rajesh T Lohiya, Krishna R Gupta (Journal of Applied Pharmaceutical Science, 2015)
A sensitive and precise high performance liquid chromatographic method has been developed and validated for determination of Dronedarone Hydrochloride. The proposed method was carried out on Analytical HPLC system consisting of Hyperchrome ODS C18 column (250 mm × 4.6 mm, 5µ). The chromatographic separation was achieved using a mobile phase containing acetonitrile: triethylamine buffer (pH-2.3) in the ratio of 70:30 v/v at flow rate of 1.0 mL/min using UV detection at 290 nm. The linear regression analysis data showed good linearity over the concentration range of 10-60µg/mL of dronedarone hydrochloride. The percent assay of dronedarone hydrochloride from tablet was found to be 99.75. The determination of intrinsic stability of the drug was assessed under acidic, alkaline, peroxide, thermal and photolytic stressed conditions. The drug was estimated in presence of its degradation products without interference. The method was validated for accuracy, precision, robustness and recovery studies as per ICH guidelines. The method can be adopted for routine analysis of drug in its tablet formulation.
Keywords: Dronedarone hydrochloride, Validation, stability indicating.